Immune response profiling in patients with traumatic injuries associated with alcohol ingestion - Adam W. Breslin; Alexander T. Limkakeng; Elizabeth Silvius; Catherine A. Staton; Chandra Almond; Mary‐Beth Joshi; Bartley Adams; Bria Johnston; Lauren McGowan; Allan D. Kirk; Eric Elster (Wiley, 2021)
Abstract Traumatic injuries afflict more than 5 million people globally every year. Current and past animal research has demonstrated association among alcohol, trauma, and impaired immune function, whereas human registries have shown association between alcohol and morbidity as well as mortality. The purpose of this study is to elucidate the immune interactions with alcohol in traumatically injured patients. We prospectively enrolled 379 patients after trauma at three medical centers in the Surgical Critical Care Initiative. Plasma was analyzed using Luminex for up to 35 different cytokines. Collected samples were grouped by patients with detectable plasma alcohol levels versus those without. Univariate testing determined differences in analytes between groups. We built Bayesian belief networks with multiple minimum descriptive lengths to compare the two groups. All 379 patient samples were analyzed. Two hundred eighty‐two (74.4%) patients were men, and 143 (37.7%) were White. Patients had a median intensive care unit length of stay (LOS) of 5.8 days and hospital LOS of 12 days. Using single variate analyses, eight different cytokines were differentially associated with alcohol. Cytokines IL‐12 and IL‐6 were important nodes in both models and IL‐10 was a prominent node in the nonalcohol model. This study found select immune function differed between traumatically injured patients with measurable serum alcohol levels as compared with those without. Traumatically injured patients with positive blood alcohol content appear less able to inhibit inflammatory stress. Alcohol appears to suppress pro‐inflammatory IL‐12 and IL‐6, whereas patients without alcohol have greater levels of anti‐inflammatory IL‐10 expressed at injury and may better regulate anti‐inflammatory pathways. Future studies should determine the relationship with these markers with clinically oriented outcomes.